2016
DOI: 10.1093/jat/bkw027
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Cannabinoid and Synthetic Cannabinoids in Dietary Supplements Using UPLC with UV and UPLC–MS-MS

Abstract: The primary purpose of this study was to develop and validate a method based on UPLC with UV and UPLC-MS-MS for the simultaneous analysis of different cannabinoids and synthetic cannabinoids in food as well as in herbal and dietary supplements. The limits of detection and quantitation of the method ranged from 0.1 to 0.3 and 0.3 to 0.9 μg/mL by UPLC with UV, respectively. The coefficient of determination was >0.999; the intra- and interday precision of the method were 0.1-3.7 and 0.9-4.1%, respectively. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Cannabinoids may be present in food and beverages, either as contaminants or as food additives (Table ). Fibre‐type C. sativa L. (hemp) is a valuable source for non‐psychoactive cannabinoids, CBD ( 3 ) being the most important one among them, usually biosynthesised in both female and male inflorescences, and these cannabinoids are used medicinally in various food, beverages and pharmaceutical preparations, as well as several cosmetics and cosmeceutical products.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabinoids may be present in food and beverages, either as contaminants or as food additives (Table ). Fibre‐type C. sativa L. (hemp) is a valuable source for non‐psychoactive cannabinoids, CBD ( 3 ) being the most important one among them, usually biosynthesised in both female and male inflorescences, and these cannabinoids are used medicinally in various food, beverages and pharmaceutical preparations, as well as several cosmetics and cosmeceutical products.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
“…During the past decade, there seems to be only two UPLC methods reported for the analysis of cannabinoids in dietary supplements, food and beverages (Table ). Heo et al reported fully validated UPLC‐PDA and UPLC‐ESI‐MS/MS methods for the quantification of THC ( 12 ) in dietary supplements, using a Waters Acquity UPLC HSS C 18 column (150 mm × 2.1 mm; particle size: 1.8 μm) and a gradient mobile phase comprising 25 mM sodium phosphate and 0.01% sodium hexane sulfonate in deionised water adjusted to pH 3 with phosphoric acid, and ACN.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
See 1 more Smart Citation
“…The amounts of solvents used are greatly reduced, and as such, the amount of waste that needs to be disposed is minimal. Obtainable efficiency and specificity by SFC are comparable to that of HPLC (Geryk et al, 2015); using HPLC/DAD (two unique analytical methods for cannabinoids and other compounds fingerprinting in Cannabis (Peschel and Politi, 2015); using HPLC, for cannabinoids analysis in -marijuana nourishments‖ (Vandrey et al, 2015); using HPLC, for doing a comparative study between THCA and THC as percentage in C. sativa, in addition to, the storage temperature effect on cannabinoids stability (Taschwer and Schmid, 2015) UHPLC By the year 2018-A liquid chromatography coupled with tandem mass spectrometry (UPLC-MS) was used for quantifying cannabinoids (THC, CBD, THCA, CBDA and CBN) concentrations in mixed olive oil cannabis preparations (Carcieri et al, 2018); Pacifici et al used UHPLC for evaluation of long-term stability of cannabinoids in standardized preparations of cannabis flowering tops and cannabis oil (Carcieri et al, 2018;Noestheden et al, 2018a;Pacifici et al, 2018); UPLC method was used for simultaneous analysis of cannabinoid and synthetic cannabinoids in dietary supplements (Heo et al, 2016); Wang et al developed and validated an UHPLC-UV-MS method for determination of 11 acid and neutral cannabinoids in cannabis samples (Wang et al, 2018). Eleven cannabinoids were characterized in Cannabis matrix using quantitative and fit-to-purpose performance as a function of extra-column variance and UPLC technique.…”
Section: Resultsmentioning
confidence: 99%
“…Various LC techniques (HPLC, UHPLC, and LC-MS) have been widely used in cannabis analysis. Complete chemical profiling of multiple compounds, including naturally occurring neutral and acid cannabinoids, can be obtained by HPLC, which requires no sample derivatization or decarboxylation [22][23][24][25][26][27][28][29]. The major drawback with LC is its inadequate resolution for the chromatographic separation of the cannabinoids in a complex plant and preparation matrices.…”
Section: Introductionmentioning
confidence: 99%